Determining the Shortest Route of Distribution to Reduce Environmental Emissions Using Saving Matrix and Nearest Neighbor Methods - Farida Pulansari; Isna Nugraha; Sinta Dewi (Nusantara Science and Technology Proceedings)
One of the problems with the Vehicle Routing Problem (VRP) is the problem of fulfilling customer requests according to the location that must be supplied from depots that have limited vehicle capacity. This also happened to Distributor PT. XYZ is located in Lamongan. Every day the distributor of PT. XYZ distributes fertilizer to several cities in East Java, one of which is in the city of Blitar. The problem that happened to the distributor of PT. XYZ does not yet have an optimal distribution route, resulting in delays in the delivery process. Optimization of distribution routes can be done by finding the shortest route in fertilizer distribution in the Blitar area. With the saving matrix and nearest neighbor method, the best route arrangement can shorten the distance and product delivery time. The final result will be savings in distribution costs because it can reduce fuel consumption for fertilizer trucks, reducing the company's variable costs and reducing environmental emissions.